The early development of International New Ventures: a multidimensional exploration. Issue 6 (2nd September 2019) - Kirwan, Paul; Ratinho, Tiago; van der Sijde, Peter; Groen, Aard J.
Abstract : Purpose: The purpose of this paper is to investigate the early development stages of International New Ventures (INVs). Specifically, the authors explore how INVs acquire and leverage four kinds of capital – strategic, managerial, financial and social – to recognise a foreign opportunity, begin the pre-foreign entry activities, and finally start the INV. Design/methodology/approach: A stage-based, multidimensional framework was used to investigate how INVs acquire and use the four capitals throughout the internationalisation process. Drawing on four case studies of high-tech INVs, this study tracks their development in three stages: foreign opportunity, pre-foreign operation and post-foreign operation. Findings: Results indicate INVs build advantages and internationalisation activities occur before formal operations begin. INVs deliberately orchestrate certain kinds of capital contingent to the specific internationalisation stage. Further, the authors find that not all types of capital are equally important throughout the internationalisation process: INVs identify foreign opportunities when endowed with managerial and social capital; INVs source a majority of their managerial and financial capitals externally before internationalising; and INVs only contribute all four capitals simultaneously after internationalising. Research limitations/implications: Findings contribute to knowledge about the development of INVs pre-internationalisation and pre-founding. The study is limited to a comparative sample of INVs, which impacts the generalisability. However, the findings provide a starting point for investigating similar effects using more representative samples. Practical implications: Entrepreneurs can be proactive in networking activities to allow them greater opportunity to interact with potential resource providers dependent on the stage of internationalisation. Originality/value: This study contributes to the international entrepreneurship literature with qualitative evidence of the micro-level processes of internationalisation. Very few studies investigate the early, pre-internationalisation and pre-foundation, development stages of INVs.